ANALISIS YURIDIS TINDAK PIDANA KEJAHATAN BISNIS : INSIDER TRADING: PERDAGANGAN SAHAM (EFEK) MELALUI ORANG DALAM - Fitriani, Agnes; Sari, Desi Puspita; Hosnah, Asmak Ul (LPPM Universitas Bina Bangsa, 2024)
The problem studied relates to specific criminal acts in the capital markets sector, namely Insider Trading or what is often known as the criminal act of securities transactions carried out illegally through 'insider' information. Legal aspects regarding criminal acts are regulated in statutory regulations in the Capital Market sector, namely in Articles 95 to 97 of Law Number 8 of 1995 concerning Capital Markets. This type of research is juridical - normative using the Library Research data collection method (library research) by examining the primary legal basis and secondary legal materials available in related legal books and other scientific written works in the form of journals, theses, Dissertation and Thesis